2015
DOI: 10.1109/mc.2015.114
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Combinatorial Testing in a Large Organization

Abstract: Introducing CombinatorialTesting in a Large Organization I n 2009, when Lockheed Martin decided to explore the benefits of combinatorial testing methods as a way to reduce testing costs and maintain competitive processes, its decision was based on several developments. That same year, pilot projects using these methods at Eglin Air Force Base in Florida were showing promise in reducing testing costs. The US Department of Defense's (DoD's) Office of Test and Evaluation had recently endorsed the design of experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Combinatorial testing has been successfully applied for testing (critical) software systems in large organizations [11]. It is an already proven method for blackbox security testing of large-scale web software systems [7], [3], [2] where t-way testing was applied successfully to XSS detection.…”
Section: Combinatorial Testing For Web Security Testingmentioning
confidence: 99%
“…Combinatorial testing has been successfully applied for testing (critical) software systems in large organizations [11]. It is an already proven method for blackbox security testing of large-scale web software systems [7], [3], [2] where t-way testing was applied successfully to XSS detection.…”
Section: Combinatorial Testing For Web Security Testingmentioning
confidence: 99%
“…One of the most commonly used strategy is pairwise (also known as two-way) testing in which each combination for all possible pairs of input parameters are covered by at least one test case. Several empirical studies [5], [6], [14], [15] on the use of combinatorial testing for industrial software have been reported and showed that pairwise testing is a very effective technique. In this paper we seek to investigate the use of pairwise testing for industrial control software and compare this technique with manual testing performed by industrial engineers.…”
Section: B Pairwise Testingmentioning
confidence: 99%
“…Pairwise testing is an approach to combinatorial testing that generates a test suite which covers each combination of value pairs at least once. There is some evidence [5], [6] suggesting that pairwise testing is efficient and effective at detecting software faults. However, even if pairwise techniques have been found useful and applicable in industrial applications, the experimental evidence regarding its effectiveness in practice is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Combinatorial testing could significantly reduce test cost and increase quality of software system [1]. It has been proved to be effective especially in a software system where faults come from the interactions of its parameters [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, this method could only be used under the condition that the value's number of each parameter in software is not larger than 2. On the basis of LDA and ELA, Hagar et al [1] propose the method of Partial Covering Array (PCA) which could be used in the software with known safe value, and it presents a new combinatorial structure to generate ELA.…”
Section: Introductionmentioning
confidence: 99%